Disputing Bodies: Queer Constructivism and Sexual Difference - Sicerone, Daniel Alberto (Universidad del Zulia, 2020)
This work is part of the contemporary debate on corporality, from the perspective of queer constructivism, and on the other, to the studies of sexual difference. These two theoretical optics bet on a clearly antagonistic corporality, since from queer constructivism the body is thought of as the moles where subjectivity occurs metaphorizing it as a battlefield where multiple forces intervene that end up being equivalent to subjectivity. On the other hand, from the studies of sexual difference, especially the Ljubljana School, the body is always a sexed body, the limit of all omnipotent pretense and fissure that causes the impossibility of a total language. The main theoretical edges of both conceptions will be addressed, as well as the consequences of the corporality dispute.